To generate greater economic benefits from visiting ships - Seow, Frank Ie Jin. (2012)
The maritime industry contributes 7 per cent to Singapore’s Gross Domestic Product (GDP). With over 140000 ships calling annually, Singapore is an ideal location for the provision of the various shipping services spreading from cargo and container handling to ship bunkering and ship repairs. This paper will focus on how to generate greater economic benefit from visiting ships to Singapore with regards to the bunker industry. Accounting for more than 60 per cent of the ship’s running costs, the cost of bunker fuel is an important issue. In view of the increasing price trend and the high demand from merchant ships, ship-owners are increasingly concerned about the quality and quantity of bunker fuel that they are getting. By reviewing past literature and studies on bunker operations, a SWOT analysis was conducted to determine the Strengths, Weaknesses, Opportunities and Threats faced by Singapore as a bunkering hub. Key issues highlighted by bunker industry professionals include bunker quantity and quality, provision of credit risk facilities, automation of bunkering operations and fraudulent practices. A combined physical and virtual bunkering hub concept is proposed involving combining physical excellence with Information Technology. The proposed concept would be able to generate greater economic benefits from ships within the shipping industry, and to make Singapore a more attractive location for business.